Reconstructing grassland fire history using sedimentary charcoal: Considering count, size and shape - Leys, B. A.; Commerford, J. L.; McLauchlan, Kendra K. (My University, 2017)
Fire is a key Earth system process, with 80% of annual fire activity taking place in grassland areas. However, past fire regimes in grassland systems have been difficult to quantify due to challenges in interpreting the charcoal signal in depositional environments. To improve reconstructions of grassland fire regimes, it is essential to assess two key traits: (1) charcoal count, and (2) charcoal shape. In this study, we quantified the number of charcoal pieces in 51 sediment samples of ponds in the Great Plains and tested its relevance as a proxy for the fire regime by examining 13 potential factors influencing charcoal count, including various fire regime components (e.g. the fire frequency, the area burned, and the fire season), vegetation cover and pollen assemblages, and climate variables. We also quantified the width to length (W: L) ratio of charcoal particles, to assess its utility as a proxy of fuel types in grassland environments by direct comparison with vegetation cover and pollen assemblages. Our first conclusion is that charcoal particles produced by grassland fires are smaller than those produced by forest fires. Thus, a mesh size of 120 mu m as used in forested environments is too large for grassland ecosystems. We recommend counting all charcoal particles over 60 mu m in grasslands and mixed grass-forest environments to increase the number of samples with useful data. Second, a W: L ratio of 0.5 or smaller appears to be an indicator for fuel types, when vegetation surrounding the site is before composed of at least 40% grassland vegetation. Third, the area burned within 1060m of the depositional environments explained both the count and the area of charcoal particles. Therefore, changes in charcoal count or charcoal area through time indicate a change in area burned. The fire regimes of grassland systems, including both human and climatic influences on fire behavior, can be characterized by long-term charcoal records.
Citation: Leys, B. A., Commerford, J. L., & McLauchlan, K. K. (2017). Reconstructing grassland fire history using sedimentary charcoal: Considering count, size and shape. Plos One, 12(4), 15. doi:10.1371/journal.pone.0176445
Keywords: Macroscopic Charcoal; Tallgrass Prairie; Regimes; Records; Holocene; Forests